Sobre el discurso alrededor de las ideas de revolución en América Latina (2018)
The ideas of revolution in Latin America have been built through the structure of hero, victim and victimizer and are contextualized within the ideas of the end of history, romanticism and freedom. Thinking about revolution also lead us to think that its content has been monopolized towards a certain way of seeing reality. To visualize and to understand the structure of thought around the idea of revolution is the main objective of this paper, which ends up wondering about the weak regional development of ideas that propose new contents to fill the concept of revolution. This writing is based on the ideas of revolution built around four historical events in the region, namely: the Mexican Revolution, which began in 1910; the Bolivian Revolution of April 1952; the Cuban Revolution, early 1959; and the Nicaraguan Revolution of the late 1970s.